NUMERICAL MODELLING APPLICATIONS ON FRACTURE PREDICTIONS: AN EXAMPLE FROM THE BLUE LIAS FORMATION IN KILVE, UK - Adi Patria (Indonesian Institute of Sciences, 2018)
Numerical modeling using Comsol Multiphysics, with Finite Element Method, has been carried out to study fracture initiation, linkage, and deflection of the Blue Lias Formation. Data were from outcrop observation where hydrofractures were well observed. Three models were set up to understand how fractures initiated, linked and arrested. The Young’s modulus of shales (Esh) was set with the value of 1 GPa, 5 GPa, and 10 GPa. The fluid excess pressure was applied with the value of 5 MPa, 10 MPa, and 15 MPa. The Young’s modulus of the limestone (Elst) was a constant at 10 GPa. The first model showed how the overburden induces fracture initiation. The results indicated that tensile stress concentrated only within limestone and favour to form fractures. The second model was about linking of fractures. The result explained that shear stress was dominantly concentrated in limestone layers. Previous hydrofractures possibly linked up forming shear fractures and en-echelon fractures. The third model was run to understand fracture propagation and deflection. The result was that tensile stress concentrated at the hydrofracture tips close to the contacts between limestone and shale. Hydrofractures were deflected, and in some places, hydrofractures were likely started to propagate through shale.Permodelan numerik dengan Comsol Multiphysics berdasarkan metode Elemen Terbatas dilakukan untuk mempelajari inisiasi, hubungan, dan defleksi rekahan Formasi Blue Lias. Data berasal dari observasi singkapan dimana hydrofracture teramati. Tiga model dibuat untuk memahami bagaimana rekahan terinisiasi, terhubung, terambatkan dan terhenti. Modulus Young’s batulempung (Esh) diatur dengan nilai 1 GPa, 5GPa, dan 10 GPa. Tekanan kelebihan cairan (fluid excess pressure) yang diterapkan sebesar 5 MPa, 10 MPa, dan 15 MPa. Modulus Young’s batugamping (Elst) konstan sebesar 10 GPa. Model pertama menunjukkan bagaimana pembebanan mempengaruhi inisiasi rekahan. Hasil perhitungan menunjukkan bahwa tekanan tarik terkonsentrasi hanya pada lapisan batugamping dan memungkinkan terbentuknya rekahan. Model kedua mengenai hubungan rekahan. Model menunjukkan bahwa tekanan geser terkonsentrasi pada lapisan batugamping secara dominan. Hydrofracture yang telah ada akan terhubung membentuk rekahan geser and rekahan en-echelon. Model ketiga dihitung untuk memahami perambatan dan defleksi rekahan. Hasilnya menunjukkan bahwa tekanan tarik terkonsentrasi pada ujung hydrofracture dekat kontak lapisan batugamping dan batulempung. Hydrofracture terdefleksi dan pada beberapa titik mulai merambat menembus batulempung.